2021
DOI: 10.3390/biomedicines9101400
|View full text |Cite
|
Sign up to set email alerts
|

The Desmin Mutation DES-c.735G>C Causes Severe Restrictive Cardiomyopathy by Inducing In-Frame Skipping of Exon-3

Abstract: Currently, little is known about the genetic background of restrictive cardiomyopathy (RCM). Herein, we screened an index patient with RCM in combination with atrial fibrillation using a next generation sequencing (NGS) approach and identified the heterozygous mutation DES-c.735G>C. As DES-c.735G>C affects the last base pair of exon-3, it is unknown whether putative missense or splice site mutations are caused. Therefore, we applied nanopore amplicon sequencing revealing the expression of a transcript wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…As research advances, more and more genes related to RCM have been discovered, such as cardiac actin (ACTC1), cardiac myosin binding protein C (MYBPC3), β-myosin heavy chain (MYH7), titin (TTN), troponin T (TNNT2), filamin-C (FLNC), αB-crystallin (CRYAB), desmin (DES), etc. (7)(8)(9)(10)(11)(17)(18)(19). In this boy, we found no other variants in genes associated with RCM, except for TNNI3.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As research advances, more and more genes related to RCM have been discovered, such as cardiac actin (ACTC1), cardiac myosin binding protein C (MYBPC3), β-myosin heavy chain (MYH7), titin (TTN), troponin T (TNNT2), filamin-C (FLNC), αB-crystallin (CRYAB), desmin (DES), etc. (7)(8)(9)(10)(11)(17)(18)(19). In this boy, we found no other variants in genes associated with RCM, except for TNNI3.…”
Section: Discussionmentioning
confidence: 66%
“…The major mutations are found in genes encoding for sarcomere proteins, such as cardiac troponins I (TNNI3), alpha tropomyosin (TPM1), titin (TTN), and so on (7). Mutations in non-sarcomeric genes are also relevant, for example in the filamin-C (FLNC), αB-crystallin (CRYAB), and desmin (DES) (8)(9)(10)(11). Here we reported a case of RCM with ventricular fibrillation in a 7-year-old boy who was successfully rescued by AED outside the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Hager and colleagues described for the first time a patient with RCM carrying the mutation DES-p.E245D. Later, it was recognized that this mutation causes a splicing defect leading to an in-frame skipping of exon-3 causing a deletion of 32 amino acids within the rod domain [115,116]. Several other pathogenic RCM-associated DES mutations have been reported [14,[117][118][119][120][121][122] (Figure 5 and Table 4).…”
Section: Desmin (Des)mentioning
confidence: 99%
“…DES variants with a pathogenic single nucleotide polymorphism located in coil 2B or near the carboxyl terminus of the gene, usually result into missense mutations that associate with conduction diseases and arrhythmias (Figure 3; Table 1). Moreover, several studies showed that single nucleotide polymorphisms (SNPs) around DES c.375G leads to a splice variant which excludes exon 3 (p.D214-E245del) (Ojrzyńska et al, 2017;Fan et al, 2019;Brodehl et al, 2021;Chen et al, 2021). The carboxyl tail of desmin has previously been suggested to play an important role in filament-filament interactions, and variations lead to filament flexibility and stiffening of the filament.…”
Section: Desmin Variants and Clinical Arrhythmiasmentioning
confidence: 99%